Atlas DCL CGIAR - Research Program on Dryland Cereals and Legumes Agri-Food Systems (DCL) - Hyman, Glenn G.; Barona, Elizabeth; Biradar, Chandrashekhar M.; Guevara, Edward; Dixon, John; Beebe, Stephen E.; Castano, Silvia; Alabi, Tunrayo; Krishna Gumma, Murali; Sivasankar, Shoba; Rivera, Ovidio; Espinosa, Herlin; et al. (2022)
This Atlas is part of DCL’s effort to set research and development program priorities. The objective is to include the geographic dimensions of DCL crop production in our overall crop and dryland systems improvement research and development. Most of the data is public domain and available online. We expect to update this Atlas in the future when new data comes available. We are especially interested in new information on biotic constraints to DCL crop production. We welcome your feedback and suggestions about how we can improve this online resource.